ON CONVERSIVE NOMINATION: ON CONVERSIVE NOMINATION - Rahimov, Abror (Журнал иностранных языков и лингвистики, 2025)
The term conversion originally comes from the field of economics, referring to the equivalence or mutual convertibility of monetary units, and is derived from the Latin word conversio. It was introduced into linguistics by G. Sweet in 1891 to describe phenomena that lead to word formation through categorical shifts and morphosyntactic adaptation according to syntactic context